Effects of Injectable Solutions on the Quality of Monocyte-Derived Dendritic Cells for Immunotherapy - Laís Teodoro Da Silva; Bruna Tiaki Tiyo; Silvia de Jesus Mota; Marina Mazzilli Ortega; Gabriela Justamante Handel Schmitz; Noemi Nosomi Taniwaki; Gislene Mitsue Namiyama Nishina; Alberto José da Silva Duarte; Telma Miyuki Oshiro (Journal of Immunology Research)
Therapeutic vaccines based on monocyte-derived dendritic cells have been shown to be promising strategies and may act as complementary treatments for viral infections, cancers, and, more recently, autoimmune diseases. Alpha-type-1-polarized dendritic cells (aDC1s) have been shown to induce type-1 immunity with a high capacity to produce interleukin-12p70 (IL-12p70). In the clinical use of cell-based therapeutics, injectable solutions can affect the morphology, immunophenotypic profile, and viability of cells before delivery and their survival after injection. In this sense, preparing a cell suspension that maintains the quality of aDC1s is essential to ensure effective immunotherapy. In the present study, monocytes were differentiated into aDC1s in the presence of IL-4 and GM-CSF. On day 5, the cells were matured by the addition of a cytokine cocktail consisting of IFN-α, IFN-γ, IL-1β, TNF-α, and Poly I:C. After 48 hr, mature aDC1s were harvested and suspended in two different solutions: normal saline and Ringer’s lactate. The maintenance of cells in suspension was evaluated after 4, 6, and 8 hr of storage. Cell viability, immunophenotyping, and apoptosis analyses were performed by flow cytometry. Cellular morphology was observed by electron microscopy, and the production of IL-12p70 by aDC1s was evaluated by ELISA. Compared with normal saline, Ringer’s lactate solution was more effective at maintaining DC viability for up to 8 hr of incubation at 4 or 22°C.